In Situ Construction of Uniform and Robust Cathode–Electrolyte Interphase for Li‐Rich Layered Oxides. (18th December 2020) - Zhao, Jingteng; Liang, Yuan; Zhang, Xu; Zhang, Zihe; Wang, Errui; He, Shiman; Wang, Boya; Han, Zhijie; Lu, Jun; Amine, Khalil; Yu, Haijun
Abstract: High‐energy‐density Li‐rich layered oxides (LLOs) as promising cathodes for Li‐ion batteries suffer from the dissolution of transition metals (especially manganese) and severe side reactions in conventional electrolytes, which greatly deteriorate their electrochemical performance. Herein, an in situ "anchoring + pouring" synergistic cathode–electrolyte interphase (CEI) construction is realized by using 1, 3, 6‐hexanetricarbonitrile (HTCN) and tris(trimethylsilyl) phosphate (TMSP) electrolyte additives to alleviate the challenges of an LLO (Li1.13 Mn0.517 Ni0.256 Co0.097 O2 ). HTCN with three nitrile groups can tightly anchor transition metals by coordinative interaction to form the CEI framework, and TMSP will electrochemically decompose to reshape the CEI layer. The uniform and robust in situ constructed CEI layer can suppress the transition metal dissolution, shield the cathode against diverse side reactions, and significantly improve the overall electrochemical performance of the cathod with a discharge voltage decay of only 0.5 mV cycle −1 . Further investigations based on a series of experimental techniques and theoretical calculations have revealed the composition of in situ constructed CEI layers and their distribution, including the enhanced HTCN anchoring effect after lattice densification of LLOs. This study provides insights into the in situ CEI construction for enhancing the performance of high‐energy and high‐voltage cathode materials through effective, convenient, and economical electrolyte approaches. Abstract : An "anchoring + pouring" synergistic strategy using 1, 3, 6‐hexanetricarbonitrile (HTCN) and tris(trimethylsilyl) phosphate (TMSP) as electrolyte additives is proposed to construct the cathode–electrolyte interphase in situ. The electrochemical stability is significantly enhanced, including a small voltage decay of 0.5 mV cycle −1 . The key "anchoring" role of HTCN is dynamically strengthened after the electrochemical transformation of the cathode with densification of transition metals.